Predictors of loss to follow up from antiretroviral therapy among adolescents with HIV/AIDS in Tanzania - Tesha, Esther-Dorice; Kishimba, Rogath; Njau, Prosper; Revocutus, Baraka; Mmbaga, Elia (PLOS ONE, 2022)
Access to Antiretroviral Therapy (ART) is threatened by the increased rate of loss to follow-up (LTFU) among adolescents on ART care. We investigated the rate of LTFU from HIV care and associated predictors among adolescents living with HIV/AIDS in Tanzania. A retrospective cohort analysis of adolescents on ART from January 2014 to December 2016 was performed. Kaplan-Meier method was used to determine failure probabilities and the Cox proportion hazard regression model was used to determine predictors of loss to follow up. A total of 25,484 adolescents were on ART between 2014 and 2016, of whom 78.4% were female and 42% of adolescents were lost to follow-up. Predictors associated with LTFU included; adolescents aged 15–19 years (adjusted hazard ratio (aHR): 1.57; 95% Confidence Interval (CI); 1.47–1.69), having HIV/TB co-infection (aHR: 1.58; 95% CI, 1.32–1.89), attending care at dispensaries (aHR: 1.12; 95% CI, 1.07–1.18) or health center (aHR: 1.10; 95% CI, 1.04–1.15), and being malnourished (aHR: 2.27; 95% CI,1.56–3.23). Moreover, residing in the Lake Zone and having advanced HIV disease were associated with LTFU. These findings highlight the high rate of LTFU and the need for intervention targeting older adolescents with advanced diseases and strengthening primary public facilities to achieve the 2030 goal of ending HIV as a public health threat.